Ophthalmic Artery Pulsatility Index Between 24–34 Weeks as a Diagnostic Predictor for Late-Onset Preeclampsia: High ROC Accuracy Despite Non-Significant Mean Differences - Meghna Deka, Saswati Sanyal Choudhury, Dibya Jyoti Gharphalia, Mandeep Bayan, Pinku Talukdar, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Late-onset preeclampsia remains a diagnostic challenge. Maternal ophthalmic arteryDoppler Pulsatility Index (PI) has emerged as a non-invasive surrogate marker for systemic vascularresistance